2022
DOI: 10.1186/s12887-022-03472-2
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity during COVID-19 in children with end-stage kidney disease: a pilot study

Abstract: Background Food insecurity, an important social determinant of health among children, has become more common during the COVID-19 pandemic. Children with chronic diseases including end-stage kidney disease (ESKD) are at higher risk of food insecurity due to their complex care needs, medication burden, and dietary restrictions. No data exists describing food insecurity prevalence in pediatric ESKD patients during the COVID-19 pandemic. Methods Food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our study adds to the literature on addressing food insecurity. Many paediatric food insecurity screening projects focus specifically on primary care clinics18–22 or individual specialty clinics 23–25. Our study includes a much larger population (>1 70 000 encounters) than the limited number of published multispecialty and multisite projects addressing food insecurity in paediatrics,26 and spans an entire 3-year study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study adds to the literature on addressing food insecurity. Many paediatric food insecurity screening projects focus specifically on primary care clinics18–22 or individual specialty clinics 23–25. Our study includes a much larger population (>1 70 000 encounters) than the limited number of published multispecialty and multisite projects addressing food insecurity in paediatrics,26 and spans an entire 3-year study period.…”
Section: Discussionmentioning
confidence: 99%
“…Many paediatric food insecurity screening projects focus specifically on primary care clinics [18][19][20][21][22] or individual specialty clinics. [23][24][25] Our study includes a much larger population (>1 70 000 encounters) than the limited number of published multispecialty and multisite projects addressing food insecurity in paediatrics, 26 and spans an entire 3-year study period. Palakshappa et al reported postintervention screening rates from 68.4% to 90.1% across six primary care practices and from 14.2% to 93.6% across individual clinicians.…”
Section: Discussionmentioning
confidence: 99%